Morphological components of white oats in soil management systems (Research, Society and Development, 2020)
The objective was to evaluate the morphological components of white oats grown in soil management systems. The work was developed at the Experimental Farm of Agricultural Sciences at UFGD, in a randomized block design, with four repetitions. The treatments consisted of the managements: EC = cross chiseling followed by harrowing; E = a scarification; EG = scarification followed by harrowing; GR = a harrowing; SM = without mobilization; PC = plowing followed by two harrows. In the white oat culture, stand, height, number of tillers, biomass, dry leaf biomass, dry shoot biomass, leaf area index, specific leaf area, leaf mass ratio and leaf area ratio were evaluated. Data analysis was performed by analysis of variance and, when significant, the Tukey test was applied at 5% probability. The white oat stand is uniform in the area and is not affected by soil management systems. The height of the oats and the number of tillers are affected by the treatments that the scarifier contains. The systems without mobilization and scarifier benefited the production of white oat biomass, as well as the dry biomass of the leaves and shoots and the leaf area index. The leaf area ratio and specific leaf area were influenced by the systems with scarifier and conventional preparation, and the leaf mass ratio by the cross scarification systems, without mobilization and conventional preparation.